2010
DOI: 10.1021/ja102145g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Structural Evolution of Medium-Sized Gold Clusters: Aun (n = 27−35)

Abstract: The structural evolution of negatively charged gold clusters (Au(n)(-)) in the medium size range for n = 27-35 has been investigated using photoelectron spectroscopy (PES) and theoretical calculations. New PES data are obtained using Ar-seeded He supersonic beams to achieve better cluster cooling, resulting in well-resolved spectra and revealing the presence of low-lying isomers in a number of systems. Density-functional theory calculations are used for global minimum searches. For each cluster anion, more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 71 publications
9
167
0
1
Order By: Relevance
“…We are aware that many theoretical and experimental studies have already been conducted for Au nanoclusters and concluded that Au nanoclusters undergo evolution with respect to size: the most stable structure of Au n clusters is planar for n < 14,22 cage for 16 ≦ n ≦ 20,11, 16 and filled structures for n > 20 21. In the present work, we placed our attention on the 1D Au nanostructures.…”
mentioning
confidence: 90%
“…We are aware that many theoretical and experimental studies have already been conducted for Au nanoclusters and concluded that Au nanoclusters undergo evolution with respect to size: the most stable structure of Au n clusters is planar for n < 14,22 cage for 16 ≦ n ≦ 20,11, 16 and filled structures for n > 20 21. In the present work, we placed our attention on the 1D Au nanostructures.…”
mentioning
confidence: 90%
“…[2][3][4][5][6][7][8][9][10] Moreover, comparison with experimental data such as a photoelectron spectrum of anionic clusters is a key step to determine the structures of the most stable clusters. For medium-sized thiolate-protected gold clusters, the generation of low-lying structures from DFT calculations is computationally very expensive.…”
Section: Information Required For Predicting the Structure Of A Complmentioning
confidence: 99%
“…87 Gao et al provided an alternative view of the multi-layer structure of Au 102 (p-MBA) 44 . From their structural analysis, the embedded Au 102 cluster was decomposed into a multi-layered structure described as Au 54 (penta-star)@Au 38 (ten wings) @Au 10 (two pentagon caps) as shown in Fig. 2.…”
Section: Information Required For Predicting the Structure Of A Complmentioning
confidence: 99%
See 1 more Smart Citation
“…What is unique about the two structures is that they both have a sizable HOMO-LUMO gap, indicating their The two Au 38 minima are also interesting in that they have two adatoms on the Au 4 @Au 32 core shell. This construction shares some similarity with the Au 35 structure where one adatom is on the Au 4 @Au 30 core shell 21 . What Au 38 's structure suggested to us is that Au 40 's structure can build upon the Au 4 @Au 32 core-shell framework but with four adatoms placed in tetrahedral symmetry.…”
Section: Fig 1 (Color Online)mentioning
confidence: 75%